Does Corporate Governance improve Financial Performance? Case of Manufacturing Companies Listed in Indonesia Stock Exchange - Ryanda Saputra; Indayani Indayani (Universitas Syiah Kuala, 2019)
Objective – This study aims to determine the effect of corporate governance on financial performance with the ownership structure as a moderating variable. Design/methodology – The sample was selected using a purposive sampling method involving manufacturing companies listed on Indonesia stock exchange for the period of 2014-2017. Financial performance is measured by ROE, corporate governance is proxied by a CGPI score between 1 - 100 which has been rated from the results of evaluating the implementation of GCG in companies by IICG, managerial ownership is calculated by comparing the number of managerial shares with the number of outstanding shares, institutional ownership is calculated by comparison of the number of institutional shares with number of shares outstanding, public ownership is calculated by comparing the number of public shares with the number of shares outstanding. The data analysis technique used is the descriptive statistical test, classic assumption test, and multiple linear regression analysis. Results – The results show that corporate governance has a significant effect on financial performance, the relationship between managerial, institutional and public ownership structures with corporate governance has a positive and significant effect on financial performance. Managerial and public ownership are not able to strengthen the effect of corporate governance on financial performance, while other variables namely institutional ownership can strengthen the effect of corporate governance on financial performance. Research limitations/implications – The conclusions drawn are only based on the selected years of observation hence it may not reflect the actual phenomenon. Another limitation is due to the companies studied were only manufacturing companies even though there are still many other companies listed on the Indonesia Stock Exchange with a longer observation period.